Some Observations on the Preparation of Platelet-Rich Plasma - Woods, Brian P.; Dennehy, Angela; Clarke, Noel (Thrombosis and Haemostasis, 1976)
In order to prepare platelet-rich plasma a constant height and volume of citrated whole blood was centrifuged at different gravity forces and times. The supernatant plasmas were examined for platelet concentrations, plasma volumes and optical densities. Results are described showing that gravity force and time have an important influence on the platelet numbers and the plasma volumes recovered.The light attenuation by different concentrations of platelets in plasma, using light path lengths of 5 mm and 10 mm, was compared. The shorter light path provides greater linearity between optical density and platelet numbers especially at higher concentrations.